Personal Branding Through Fashion Blogging - Safitri, Yuanita (Humaniora, 2017)
The objective of this research was to analyze personal branding development from personal brand identity, personal brand positioning, and personal brand assessment. The object of this research was Diana Rikasari's blog “Hot Chocolate and Mint”. She is one of prominent influence and fashion blogger from Indonesia. The research used the qualitative method with data collection by virtual observation from June until August 2016. Rikasari’s personal branding showed on her blog was the fashionably smart woman who had entrepreneurship competence. This research finds out that Diana Rikasari success to make her personal identity by her blog profile and blog posting. Her positioning is clear as Indonesian modern woman. The personal brand assessment can be seen through the achievements and feedbacks on her blog post, both positive or negative.